Komunikasi dan Gaya Kepemimpinan - Muspawi, Mohamad; Vilanti, Friska Aqilah; Ekayani, Pusparatri (Universitas Batanghari Jambi, 2024)
This article presents information about communication in organizations along with the theory of leadership styles in organizations. The method used is using the Library Research method. Communication within an organization can be defined as the process of exchanging information, ideas, thoughts, and views between individuals or groups within an organization. It is important for an organization to have an effective and structured communication system, and ensure that all members of the organization understand the importance of good communication in achieving common goals. Leadership styles include authoritarian style, democratic style, free style, paternalistic style, and militaristic style.